ARTIFICIAL CIVILIZATION AND THE HISTORICAL DEVELOPMENT OF CIVILIZATION THEORY - Fahmi Irhamsyah; Maria Ulfah Anshor (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
Indonesia is entering an era where artificial intelligence (AI) is entering the life of the nation's civilization. Academic studies as material for making regulations related to the use of AI in the joints of the nation's life have not been carried out much. One of the important theories in the academic study of civilization is the basic theories of civilization discussed by Braudel and Kabuye Uthman Sulaiman. Fernand Braudel and Kabuye Uthman Sulaiman are two civilization theorists who represent old and contemporary mindsets, both of these thoughts if critically examined in the context of the 21st century when the world began to enter artificial civilization turned out to have some notes. The results of the research conducted on these two figures' thoughts found that thoughts about the theory of civilization need to be reviewed so that social science and humanities academics are able to analyze AI problems in the context of civilization